Menelusuri Kontroversi Klaim Budaya Perspektif Indonesia-Malaysia dalam Sengketa Warisan Budaya - Hasanah, Uswatun; Magfirah, Royyan; Setiawati, Andini; Nurhasanah (Indo-MathEdu Intellectuals Journal, 2024)
This article reviews the cultural claims controversy between Indonesia and Malaysia in cultural heritage disputes. This study aims to explore the long debate between Indonesia and Malaysia regarding competing cultural claims. This article uses the research method of literature study or literature study by collecting data and information using various library resources, including books, documents, and periodicals, and archival narratives. Data collection is carried out by collecting various scientific articles from research published through google scholar. Data search was carried out using keywords relevant to the focus of this study. Data analysis is carried out qualitatively with stages of data reduction, data presentation, and conclusion drawing. The results of the data analysis show that tracing the controversy over cultural claims between Indonesia and Malaysia in cultural heritage disputes, illustrates the complexity of dynamics between the two countries involving aspects of history, politics, and cultural identity. Competition for claims to cultural heritage often reflects efforts to strengthen or expand national identity, while also fighting for economic rights and interests. Such conflicts emphasize the need for a cautious and evidence-based approach in resolving claims, while considering the importance of close bilateral cooperation to preserve and promote the cultural richness that forms part of a shared identity within the Southeast Asian region